Fiscal Accounting of Bank Restructuring - Wolfe, Andy (IMF Policy Discussion Papers; Policy Discussion Paper, 1997)
Current guidelines and practice for classifying government bank assistance operations inadequately capture in the fiscal balance some of the most common, and important, operations. The shortcomings result from the focus on the general government, the exclusion of non-cash operations, and divergences between the timing of cash outlays and the economic impact of assistance operations. Complementing the standard measures of the fiscal balance with an 'augmented' balance would provide a definition that is transparent, comprehensive, and reasonably comparable across countries. The augmented balance would explicitly incorporate the major quantifiable fiscal costs of bank assistance operations that are not already included in current definitions of the overall balance.